Nutritional approach for increasing public health during pandemic of COVID-19: A comprehensive review of antiviral nutrients and nutraceuticals - Vahideh Ebrahimzadeh-Attari; Ghodratollah Panahi; James R. Hebert; Alireza Ostadrahimi; Maryam Saghafi-Asl; Neda Lotfi-Yaghin; Behzad Baradaran (Tabriz University of Medical Sciences, 2021)
Background: The novel coronavirus (COVID-19) is considered as the most life-threatening pandemic disease during the last decade. The individual nutritional status, though usually ignored in the management of COVID-19, plays a critical role in the immune function and pathogenesis of infection. Accordingly, the present review article aimed to report the effects of nutrients and nutraceuticals on respiratory viral infections including COVID-19, with a focus on their mechanisms of action. Methods: Studies were identified via systematic searches of the databases including PubMed/ MEDLINE, ScienceDirect, Scopus, and Google Scholar from 2000 until April 2020, using keywords. All relevant clinical and experimental studies published in English were included. Results: Protein-energy malnutrition (PEM) is common in severe respiratory infections and should be considered in the management of COVID-19 patients. On the other hand, obesity can be accompanied by decreasing the host immunity. Therefore, increasing physical activity at home and a slight caloric restriction with adequate intake of micronutrients and nutraceuticals are simple aids to boost host immunity and decrease the clinical manifestations of COVID-19. Conclusion: The most important nutrients which can be considered for COVID-19 management are vitamin D, vitamin C, vitamin A, folate, zinc, and probiotics. Their adequacy should be provided through dietary intake or appropriate supplementation. Moreover, adequate intake of some other dietary agents including vitamin E, magnesium, selenium, alpha linolenic acid and phytochemicals are required to maintain the host immunity.